The Mask of the ‟Odessa Beaumond”: Poetry of Borys Necherda - Polishchuk, Yaroslav (Poznańskie Studia Slawistyczne, 2020)
There are analysed in the article writings of the Ukrainian poet Borys Necherda (1939-1998). He was the original writer of the generation of 1960th and made brave experiments with the artistic word. Necherda as an author balanced between the official literature and the literature of the underground. There are a lot of unconventional features in his poems such as colloquial vocabulary, elements of slang, journalism, mixing of discourses and various means of rhetoric. That was a reason that Necherda’s writings were not appreciated during his life. Only nowadays after the poet’s death we have the possibility to re-read it from new points of view. This writings evidence a process of vanguard experimenting. In an original way they present a local peculiarity of a place: the poet become the voice of the „Odessa beaumond”, choosing masks for his lyrical subject.